Sciatic nerve injury treated by acupuncture: a bibliometric study and visualization analysis - Wang, Yan; Wang, Yan; Pei, Fei; Wang, Yahui; Lv, Lijie; Li, Tianyi; Wang, Shujin; Qin, Huan (Frontiers in Neurology, 2024)
ObjectiveSciatic nerve injuries often lead to severe pain and motor dysfunction, causing serious impact on patients’ quality of life. Acupuncture, as one of the main therapies in traditional Chinese medicine, is gradually gaining attention in the field of nerve injury due to its potential role in pain relief and nerve repair. Bibliometric and scientific knowledge mapping methods were employed to analyze the current research status, hotspots, and development trends of acupuncture for sciatic nerve injury (SNI) over the past decade.MethodsA literature search was conducted on acupuncture for SNI from the China Knowledge (CNKI), Wanfang, Weipu (VIP), and Web of Science (WOS) databases, and CiteSpace V6.R6 software and VOSviewer1.6.20 software were employed to analyze and visualize keywords from the collaborative network, keyword co-occurrence, and keyword timeline, respectively. Keyword emergence was analyzed and visualization maps were drawn.ResultsA total of 907 articles were included in the Chinese database, while 78 articles were included in the WOS database. The leading institutions of the literature in Chinese and English were the Liaoning University of Traditional Chinese Medicine and the Institute of Acupuncture and Moxibustion, respectively. Ma Tieming is the most influential person in the field. A keyword analysis of the Chinese and English literature revealed that Huanjiu and Huizhong points are commonly used and that acupuncture is often applied with drug therapy, physical therapy, and rehabilitation training, which can improve the treatment effect comprehensively. Additionally, the therapeutic mechanism of acupuncture mainly promotes nerve regeneration and repair through the modulation of cytokines and related signaling pathways. Electroacupuncture and neuropathic pain are cutting-edge research topics in this field. Based on the keyword emergence, it is predicted that future studies will continue to focus on acupuncture treatment, functional recovery after SNI, and spinal cord injury, which may become the research hotspots in this field. In addition, future studies could further delve into the selection and physiological mechanisms of acupuncture points and validate the effectiveness of this acupuncture and its integrative therapeutic strategies through a wider range of clinical practices.ConclusionThis study uses visualization software VOSviewer and CiteSpace to provide the current status and trends in SNI of acupuncture over the past decade and predicts potential research frontiers and hot directions.